Antiphospholipid Syndrome: Diagnostic Aspects of Lupus Anticoagulants - Arnout, J. (Thrombosis and Haemostasis, 2001)
Antiphospholipid syndrome (APS) is an autoimmune disorder in which antiphospholipid antibodies (aPL) are thought to be involved in the development of venous and/or arterial thrombosis. APL found in this syndrome are antibodies directed against a variety of phospholipid (PL) binding-proteins of which β2-glycoprotein I (β2GPI) and prothrombin are considered to be the major antigens. Some of these antibodies prolong PL-dependent clotting reactions and are termed lupus anticoagulants (LA). Autoimmune aPL which bind through β2GPI to cardiolipin are called anticardiolipin antibodies (aCL). Clinical studies indicate that LA is a stronger risk factor for thrombosis than aCL. The production of monoclonal antibodies against β2GPI and prothrombin has enabled us to understand the mechanism by which LA prolong coagulation in vitro. LA form bivalent antigen-antibody complexes with increased affinity for PL which compete with coagulation factors for the same catalytic surface. These LA positive monoclonal antibodies may be helpful in further improving the laboratory diagnosis of LA.
Keywords: Lupus anticoagulant; antiphospholipid antibodies; beta-2-glycoprotein I; antiprothrombin antibodies